COMPARATIVE ANALYSIS OF PERFORMANCE BETWEEN ECMP AND NTH METHODS IN IMPLEMENTATION OF MICROTIC-BASED DUAL LINK LOAD BALANCING TECHNIQUES - Dian Novianto; Yohanes Setiawan Japriadi (LPPM STMIK Pringsewu, 2021)
Load balancing is a technique within the network that functions to divide the network into two or more links with the aim that internet access needed by clients on the network does not experience problems. However, there are various methods that can be used in the load balancing technique, so it is necessary to test the performance of these methods in order to choose which method has better performance. In this study, the methods implemented in the load balancing technique are ECMP and NTH. The research methodology used is qualitative and comparative, and PPDIOO as a network development model. By applying the comparative method, there is a comparison of the results of testing load balancing techniques using the ECMP and NTH methods. Testing is done by downloading files in two different sizes, with criteria less than 100 MB and more than 100 MB. Performance analysis of Quality of Service (QoS) is based on four parameters. There are throughput, delay, jitter and packet loss. The results of the Quality of Service (QoS) load balancing technique are the best after being tested and compared based on predetermined parameters. It concludes that the NTH method is slightly better than ECMP because it has a slightly larger throughput value.